Contemporary Prophetic and Deliverance Ministry Challenges in Africa. (October 2019) - Tsekpoe, Christian
This paper contends that in Africa, the belief in the reality of the spirit world is a persistent phenomenon, which occupies a significant place in their religiosity. By building their theologies around the existential needs of the African people, the prophetic and deliverance ministries represent a contextual approach to Christianity in Africa. Nevertheless, an examination of the strengths and weaknesses of these ministries reveal that their approach may fit well into the African cultural milieu, but their emphasis is a threat to the progress of Christian discipleship in Africa and among Africans in the diaspora. Despite their rapid numerical growth, the deliverance ministries cannot bring the African out of the fear of witchcraft and other supernatural powers. The paper concludes that to be able to mitigate the challenges of these ministries, pragmatic solutions being discussed at the academic levels must be made accessible to grassroots prophets.